Avaliação do papel das células B na hanseníase experimental - Marques, Heloisa (2018)
Leprosy is a chronic infectious disease that mainly affects skin and peripheral nervous system, whose etiologic agent is the bacillus Mycobacterium leprae. Based on the clinical and histopathological characteristics, leprosy can be classified into two polar forms (tuberculoid and lepromatous), three intermediate or borderline forms (borderline-tuberculoid, borderline- borderline and borderline- lepromatous) and two reactional events (Type I and II). This broad spectrum of clinical forms is directly related to cellular immune response, with the influence of Th1, Th2, Th17 and regulatory T cells. Recently, B cells have also been described as important immunoregulatory elements, since they can produce different classes of cytokines and currently subdivided into effector B cells and regulatory B cells. Preliminary results from our group demonstrated that BKO knockout mice exhibit significantly larger bacillary plantar cushions than wild animals (WT), demonstrating the importance of such cells in experimental leprosy. The present study evaluated the expression of cytokines related to the immunopathology of leprosy (IFN-gamma, TNF-alpha, IL-4, IL-17, TGF -beta and IL-10) in the plantar cushions and lymph nodes of the BKO and WT mice. Additionally, to characterize the inflammatory infiltrate, the subpopulations of macrophages M1 and M2 present in the plantar cushions of both groups were phenotyped using the immunohistochemical technique. The results obtained demonstrated that expression of IL-4, IL-10 and TGF-beta cytokines was significantly higher in the BKO plantar cushions when compared to the WT group, but there was no difference in IFN-gamma, TNF-alpha and IL-17. In addition, in the lymph nodes, only IL-17 expression was significantly higher in the WT group. As for the inflammatory infiltrate, the number of M1 macrophages was significantly lower in the BKO group when compared to the WT group, whereas the number of M2 macrophages was significantly higher in the BKO and WT groups when compared to the M1 macrophages. The results obtained in this study demonstrated that the absence of B lymphocytes contribute to the persistence and multiplication of the bacillus, probably due to the increased expression of the IL-4, IL-10 and TGF-beta cytokines, as well as a decrease in the number of M1 macrophages in the inflammatory site.